ANALYZING PURCHASE INTENTION ON ONLINE FASHION THRIFT STORE - Gloria Lumenta; Maryam Mangantar; Merinda H. C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this research is to analyze what attracts customer purchase intention in the Online Fashion Thrift Store. This research is descriptive qualitative research. Informants in this study are sellers of online fashion thrift store that joined the social media community, “Klontong Manado (Online Shop Sulut)”, whom have been actively selling fashion products for a minimum six month-long. The second type of informants is the consumer that had made purchase inside the community at least once. Analysis method in this study will use Miles and Huberman analysis technique for qualitative research, which are data reduction, data display, and then drawing conclusion. Based on the result provided, it is concluded that the variables, which are perceived risk, perceived benefit, trust, brand image, and price are positively influence customer purchase intention considering the agree responses is more than other result such as doubtful and disagree. Although there are several responses go toward competing with agree responses, the agree responses is always more than half. Price and perceived benefit are the most agreeable variables influencing customer purchase intention. It is concluded that every variable is agreeable to be creating or improving customer purchase intention in general   Keyword: purchase intention